If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 69.8x + 42 = 65 Reorder the terms: 42 + 69.8x = 65 Solving 42 + 69.8x = 65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 69.8x = 65 + -42 Combine like terms: 42 + -42 = 0 0 + 69.8x = 65 + -42 69.8x = 65 + -42 Combine like terms: 65 + -42 = 23 69.8x = 23 Divide each side by '69.8'. x = 0.329512894 Simplifying x = 0.329512894
| 12/k=24k | | 120x+10=150x+4 | | 4x(2)-6x= | | 69.8+42=65 | | 2(x+3)+1=15 | | 56.80x+25.50=78x+100 | | 8x-15y=34 | | A=150*sqrt(3) | | 2(x+1)-5x=2x-8 | | F(x)=x/5-2x | | (2x-3y)(3x+6y)=0 | | 2x-5/6=6 | | (x-y)(x+2y)=0 | | x=2x^2+8x-16 | | (5-1)-2=5-(1-2) | | s-0.2=48 | | 6x+9=9-(3x-5) | | 6xy*5xy+5x= | | f(-3)=9-4 | | t^2+11+24=0 | | 2(r-7)-(r-8)=3 | | 7+25=18+x | | X-3+2x=x+5 | | 7(4x-2)=5(2-x) | | x+25+x+-5=90 | | (2.4)(2.0)=(X)(0.5) | | 2(3.14)14= | | -(x+8)=-9x+56 | | (2c+5)(c+4)=0 | | 7+3y=18+x | | 3e-x-1=5 | | -16x^2+80= |